Effects of plant growth regulators on eggplant seed germination and seedling growth - Neto, Francisco José Domingues [UNESP]; Dalanhol, Samanta Jaqueline [UNESP]; Machry, Marcos; Junior, Adilson Pimentel [UNESP]; Rodrigues, João Domingos [UNESP]; Ono, Elisabeth Orika [UNESP] (Southern Cross Publishing, 2017)
This study aimed at evaluating the germination and the growth of eggplant (cultivar 'Embu') seedlings submitted to imbibition in GA3 and GA4+7+Benzyladenine (BA). The experiment was carried out under laboratory and greenhouse conditions, adopting a completely randomized design, in a 2 x 6 factorial arrangement, i.e. two plant growth regulators (GA3 and GA4+7+BA) and six imbibition conditions (no imbibition, 0, 250, 500, 750, and 1000 mg L-1 a.i.). Germination percentage, mean germination time, germination speed index, first germination count, synchronization index, and germination frequency were determined in the laboratory. In greenhouse, evaluations consisted of emergence speed index, seedling height at 15, 30, and 45 days after imbibition; stem diameter at substrate surface level, leaf area, root and shoot dry matter, and Dickson quality index at 45 days. GA3 accelerated the seed germination process and the seedling emergence, and led to an increase in seedling height at 750 mg L-1 up to 30 days. For the mixture GA4+7+BA, the results indicated phytotoxic effects, delaying seed germination and seedling formation. Thus, pre-soaking of eggplant seeds in GA3 at 750 mg L-1 is recommended.
Keywords: GA3; GA4+7+Benzyladenine; Solanum melongena L.